2000
DOI: 10.4141/p99-094
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of nitrogen application via a trickle irrigation system with surface banding of granular fertilizer on red raspberry

Abstract: . 2000. Comparison of nitrogen application via a trickle irrigation system with surface banding of granular fertilizer on red raspberry. Can. J. Plant Sci. 80: 363-371. A field trial compared applications of ammonium nitrate N as soil-surface bands of granular fertilizer with applications as a solution through a trickle irrigation system (i.e., fertigation) on yield, plant growth and end-of-season extractable soil inorganic nitrogen of red raspberries (Rubus idaeous L.). The granular application was made once … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
3
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 11 publications
(17 reference statements)
2
18
3
1
Order By: Relevance
“…To be able to evaluate nitrate leaching during the growing season, knowledge of irrigation practices is a prerequisite [26]. However, in the study area, farmers often do not have accurate information to allow for best timing of irrigation; they lack the necessary triggers to start and end irrigation.…”
Section: The Growing Seasonmentioning
confidence: 99%
“…To be able to evaluate nitrate leaching during the growing season, knowledge of irrigation practices is a prerequisite [26]. However, in the study area, farmers often do not have accurate information to allow for best timing of irrigation; they lack the necessary triggers to start and end irrigation.…”
Section: The Growing Seasonmentioning
confidence: 99%
“…Previous studies in the Lower Fraser Valley have found limited response of raspberry to N fertilization (Dean et al 2000;Zebarth et al 2001); however, Kowalenko (1981a) found a small but significant increase in cumulative berry yield measured over four growing seasons. Similarly, Kowalenko, Keng, and Freeman (2000) measured significant effects of N treatments only in the last two of four successive years in which the treatments were applied.…”
Section: Introductionmentioning
confidence: 99%
“…A aplicação de N geralmente é feita na forma granular e na linha de plantio, mas pode ser realizada via fertirrigação ou adubação foliar (Strik, 2008;Freire, 2007). Kowalenko et al (2000), em estudo de comparação entre os métodos de aplicação, concluíram que a adubação granular na primavera surtiu melhor resultado que a fertirrigação por gotejamento, principalmente devido à maior lixiviação observada no método por gotejamento. Embora possa ser utilizada, a adubação foliar não tem apresentado resultados satisfatórios (Hart et al, 2006), o que se justifica pela alta demanda que a planta possui em relação a este nutriente.…”
Section: Introductionunclassified